Effects of vineyard agricultural practices on the diversity of macroinvertebrates - Joaquina Ramos, Isabel (2018)
In Europe, agriculture represents the dominant land use and there is a substantial part of biodiversity associated with those habitats. Therefore, conservation studies should direct to agriculture fields aiming to minimize the biodiversity losses. Vineyards could play a key role in producing win-win solutions for agriculture and biodiversity conservation, as an entrance point of sustainable practices in agriculture management. This study aims to evaluate the influence of different agriculture practices on macroinvertebrate diversity and in the productivity of the vineyards. Comparing these variables, we hope to determine the most sustainable agriculture practices, to suggest conservation measures to enhance sustainability and improve biodiversity in the vineyards. We are comparing Coleoptera, Hymenoptera and Hemiptera diversity and levels of productivity in three differently managed vineyards: conventional, organic and integrated production with controlled doses of chemicals (optidose). Macroinvertebrates will be sampled by pitfalls and colour plates. Study area is Herdade dos Pinheiros of Fundação Eugénio de Almeida, in Évora (Alentejo, Portugal). We expect to find higher macroinvertebrates diversity where there is less disturbance, as in the organic vineyard. And the contrary for the conventional. Also, we are expecting to find little diversity of Hemiptera when there are higher levels of Coleoptera and Hymenoptera diversity, because that means biological control is acting. Finally, we hope to find the best agriculture measures to enhance sustainability and improve biodiversity in vineyards and surrounding areas.